REKONSTRUKSI KEWENANGAN BAWASLU TERHADAP PELANGGARAN ADMINISTRATIF PILKADA (STUDI PUTUSAN MK NO. 104/PUU-XXIII/2025) - Novemyanto, Alfin Dwi (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
The disharmony in the regulatory framework governing Bawaslu’s authority between the General Election and Regional Election regimes creates legal uncertainty and weakens the effectiveness of administrative violation enforcement, primarily due to the divergence between binding “decisions” and non-executory “recommendations.” This discrepancy undermines procedural justice and reduces the reliability of election oversight mechanisms intended to safeguard fairness and integrity. This study aims to analyze the normative inconsistency contained in Articles 139 and 140 of the Regional Election Law and to formulate a reconstruction model that strengthens Bawaslu’s authority in accordance with constitutional principles and contemporary electoral governance needs. Using normative juridical and conceptual approaches, this research examines statutory regulations, Constitutional Court Decision No. 104/PUU-XXIII/2025, and relevant scholarly literature. The findings reveal that the existing dualism of authority creates institutional subordination and obstructs effective administrative enforcement, thereby necessitating the strengthening of Bawaslu’s adjudicative powers supported by enforceable mechanisms and a structured administrative appeal system. Such reconstruction is essential to reinforce electoral integrity and to establish a coherent and just legal framework governing regional elections.